Sulfonic acid functionalized mesoporous silicas and organosilicas: synthesis, characterization and catalytic applications - Shylesh, S.; Samuel, Prinson P.; Srilakshmi, Ch.; Parischa, Renu; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2007)
Ethane bridged mesoporous organosilicas and MCM-41 having sulfonic acid groups in the pore channels were prepared by co-condensation method as well as grafting method, using 3-mercaptopropyltriethoxysilane (3-MPTS) as the sulfur precursor. TEM and N-2 sorption isotherm analysis revealed that the mesoporous structural ordering is retained after the functionalization and modifications of organic groups while FT-IR, Raman, XPS and solid-state C-13 CP MAS NMR shows the presence of sulfonic acid groups and the stability of the mesoporous framework. The catalytic activity of the developed materials was evaluated in the liquid phase Claisen-Schmidt condensation reaction of acetophenone with benzaldehyde, to probe the effect of mesoporous support surfaces as well as the role of preparation methods. Results showed that sulfonic acid functionalized ethane-silica samples were more active, selective and stable than the conventional sulfonic acid containing mesoporous catalysts. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: condensation; ethane-silica; heterogeneity; sulfonic acids

Synthesis of hydrothermally stable aluminium-containing ethane-silica hybrid mesoporous materials using different aluminium sources - Shylesh, S.; Samuel, Prinson P.; Singh, A. P. (Microporous and Mesoporous Materials, 2007)
Aluminium-containing ethane-silica hybrid mesoporous materials having ethane groups in the frame wall positions are synthesized using aluminium isopropoxide as well as aluminium nitrate as the aluminium sources. The materials were characterized in detail using powder XRD, N-2 adsorption-desorption, SEM, TEM, TG-DTG, TPD, Si-29, C-13 and Al-27 MAS NMR techniques. Characterization techniques revealed that aluminium isopropoxide was the appropriate source for the synthesis of organo aluminosilicas on considering the structural ordering, acidity as well as the percentage of aluminium incorporation into the ethane bridge. Al-27 MAS NMR displays aluminium as tetrahedrally coordinated in both the aluminium-containing organosilicas. Unlike the conventional EtOH-HCl template extraction process, in the present studies, we had used EtOH-NH4OH as the surfactant-extracting medium and chemical analysis results suggest that using this procedure the extent of dealumination can be greatly reduced. XRD and nitrogen physisorption studies further proved that the materials are hydrothermally stable, that the ordered pore channels retains its structure even after 150 h reflux in boiling water, while the conventional Al-MCM-41 catalyst collapsed its mesostructure after 50 h reflux in water. The improved hydrothermal stability of the hybrid materials, even in presence of sodium ions, is attributed to the thick pore walls as well as due to the presence of hydrophobic bridging ethane groups in the wall positions. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Al-HMM; Al-MCM-4l; hybrid materials; Hydrothermal stability